Standardization of Proper Volume/size and Type of Root Trainer for Raising Dalbergia sissoo Seedlings: Nursery Evaluation and Field Trial - Ginwal, H. S.; Rawat, P. S.; Sharma, Sandeep; Bhandari, A. S.; Krishnan, C.; Shukla, P. K. (Indian Forester, 2001)
Seedling quality is a key factor in the success of any tree plantation programme, which ultimately depends upon the root system. Root trainers are increasingly being used to deal with the problem of root coiling and distortion commonly encountered in polybag grown seedlings. Due to the lack of species specific results for Indian conditions and species, root trainers are still at the initial stage of use in Indian nurseries. In the present investigation, a multivariate approach has been adopted to find out the right size/volume and type of root trainer for raising Dalbergia sissoo seedlings in the nursery. Root trainers of various type and cell sizes like Hiko trays 90 cc, 150 cc, 300 cc, Book type 200 cc and single cell bullet type 290 cc were tried and the growth and biomass production of D. sissoo seedlings in 3 months time period was studied. The quality parameters of seedlings in various treatments were figured out. The seedlings raised under different size and type of root trainers were also observed in the field for two consecutive years. Though the Hiko tray 300 cc cell volume scored maximum points in respect of seedling quality parameters upto the nursery stage, field performance of Hiko tray 150 cc volume was found the best. The Hiko tray 150 cc cell volume raised seedlings achieved maximum plant height and collar diameter after field planting although the performance of Hiko tray 300 cc and 150 cc cell volume was statistically at par in respect offield survival. The results have indicated that though the nursery stage growth performance has scored maximum points in respect of Hiko tray 300 cc cell volume due to greater space available for the root system, the field performance of 150 cc volume is significantly better than the 300 cc one. Thus the Hiko tray 150 cc volume is the best size/volume and type of root trainer for raising D. sissoo seedlings in nursery. The Hiko tray 300 cc volume comes out in the second category.